A Comparison of English and Mandarin-Speaking Preschool Children’s Imitation of Motion Events - Wang, Zhidan; Wang, Haijing (Frontiers in Psychology, 2017)
Typically in English, a “satellite-framed” language, manner is expressed in the verb and path is expressed in supporting words. Past studies using looking time techniques suggest that English-speaking 3-year-olds show language-specific action processing, but 2.5-year-olds preferentially attend to path regardless of native language. In Study 1, we test whether language-specific action component preferences will be reflected in children’s imitation, as a more explicit measure. Children who spoke English saw an adult move an object along a series of platforms using one of two paths and manners. Then, the children were given the opportunity to move the object on a different test platform, which was designed to force them to choose to reproduce either the demonstrated path or the manner. The results showed that 3-year-olds, but not 2.5-year-olds, were more likely to imitate the manner versus the path. In Study 2,we extend the investigation to a less commonly studied language within this domain, Mandarin. Typically in Mandarin, an “equipollently-framed” language, both manner and path are expressed within equally significant verbs. The results indicated that 3-year-olds did not show a consistent preference to imitate either the path or the manner. In contrast, 2.5-year-olds were more likely to imitate the path than the manner. This research highlights the potential for the imitation choice paradigm, as an explicit measure, to understand how language affects cognition, and suggests a new language-specific pattern in action interpretation.